Impact of Attention Deficit and Hyperactivity Disorder (ADHD) on Behavior and Cognitive Profile in Children with Specific Learning Disability (SLD) - Dr. Ajit Chandanshive; Anita Vinod Chitre (International Journal of Indian Psychȯlogy, 2022)
Background: Attention deficit and hyperactivity disorder (ADHD). is the most commonly co-occurring condition with Specific learning disability (SLD). ADHD and SLD has specific cognitive deficiencies and behaviour challenges. Understanding the differences and potential overlap between them can guide targeted intervention. Purpose of the study is to examine the difference in behaviour and cognitive profile in children diagnosed with SLD and children diagnosed SLD with comorbid ADHD. Method: Sample consisted of 32 children in the age group between 8 to 12 years diagnosed with SLD only (Group 1) and SLD with Comorbid ADHD (Group 2). Behaviour profile were compared using scores on Child behaviour checklist completed by parents for Group 1 and Group 2. Difference in behaviour problems between two groups were assessed using Mann Whitney U test. Cognitive profile was compared using WISC IV index score, General Ability Index (GAI), Cognitive proficiency Index (CPI) for Group 1 and Group 2, a t test was used. Results: Children diagnosed with SLD and comorbid ADHD show significantly higher behaviour problems than children diagnosed with SLD only, U= 30.50, p<.001. Overall, Children with SLD were found to have significant strength in GAI and weakness in CPI, however no significant difference in cognitive profile was observed between the Groups. Conclusion: The findings suggest that co-occurrence of ADHD in children with specific learning disability can exacerbate behaviour issues in children with specific learning disability. ADHD does not significantly affect the cognitive profiles in children with SLD.